The Oral Health Inequities between Special Needs Children and Normal Children in Asia: A Systematic Review and Meta-Analysis - Ningrum, Valendriyani (Healthcare (Basel), 2021)
This meta-analysis aimed to analyze the oral health inequalities among special needs children during 2004–2019 in Asia to reveal the importance and the needs of establishing integrated and equitable special needs dentistry care system in Indonesia. PubMed, Scopus, Cochrane Library, Web of Science, and Wiley Online Library were systematically searched for full-text observational studies published from 1 January 2004 to 15 January 2020, in English in Asia. Studies that included children under 18 years of age with special needs and compared them to healthy controls were selected. Study quality was assessed using the Joanna Briggs Institute 2017 Critical Appraisal Checklist. Risk of bias was assessed using the ROBINS-E tool. The decayed, missing, and filled permanent teeth (DMFT) index indicated that special needs children who suffer from intellectual disability or autism spectrum disorder had significantly more caries than normal children (p < 0.001). The special needs children who had more caries than normal children lived in countries that had a high average DMFT value among 12 years old children (p < 0.001), and these two variables showed a positive correlation in meta-regression analysis (p < 0.001). Having an integrated and equitable care system and elevating children’s oral health are important to maintain special needs children’s oral health.